Effect of repetitive pecking at working length for glide path preparation using G-file - Jung-Hong Ha; Hyo-Jin Jeon; Rashid El Abed; Seok-Woo Chang; Sung-Kyo Kim; Hyeon-Cheol Kim (Korean Academy of Conservative Dentistry, 2015)
Objectives Glide path preparation is recommended to reduce torsional failure of nickel-titanium (NiTi) rotary instruments and to prevent root canal transportation. This study evaluated whether the repetitive insertions of G-files to the working length maintain the apical size as well as provide sufficient lumen as a glide path for subsequent instrumentation. Materials and Methods The G-file system (Micro-Mega) composed of G1 and G2 files for glide path preparation was used with the J-shaped, simulated resin canals. After inserting a G1 file twice, a G2 file was inserted to the working length 1, 4, 7, or 10 times for four each experimental group, respectively (n = 10). Then the canals were cleaned by copious irrigation, and lubricated with a separating gel medium. Canal replicas were made using silicone impression material, and the diameter of the replicas was measured at working length (D0) and 1 mm level (D1) under a scanning electron microscope. Data was analysed by one-way ANOVA and post-hoc tests (p = 0.05). Results The diameter at D0 level did not show any significant difference between the 1, 2, 4, and 10 times of repetitive pecking insertions of G2 files at working length. However, 10 times of pecking motion with G2 file resulted in significantly larger canal diameter at D1 (p < 0.05). Conclusions Under the limitations of this study, the repetitive insertion of a G2 file up to 10 times at working length created an adequate lumen for subsequent apical shaping with other rotary files bigger than International Organization for Standardization (ISO) size 20, without apical transportation at D0 level.